PENGARUH JENJANG PENDIDIKAN, SKALA USAHA DAN LAMA USAHA TERHADAP SISTEM INFORMASI AKUNTANSI PADA UMKM TANGERANG SELATAN - Sulistyanto, Dwi (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2024)
This study aims to determine the effect of education level on accounting information systems, to determine the effect of business scale on accounting information systems, to determine the effect of business duration on accounting information systems. The variables in this study are education level, business scale, and business duration as independent variables, then accounting information systems as dependent variables. This study uses primary data with a sample size of 100 respondents. The analysis method used in the study is multiple linear regression. The results of this study are that business level and duration have a positive effect on accounting information systems, while business scale does not affect accounting information systems.